Association between stress and socioeconomic characteristics in college students.. - Silas Alves da Silva, Filipe Melo da Silva, Haylla Simone Almeida Pacheco, José Wictor Pereira Borges (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/2238-7234.8426-33